Content Analysis of Socio-Scientific Issues Research in Physics Learning 2020-2025: Systematic Literature Review - Indraswari, Anisa Wulan; Wahyuni, Siti (Universitas PGRI Semarang, 2025)
This study aims to identify trends and directions of studies related to the socio-scientific issues (SSI) approach in physics education. Using the Systematic Literature Review (SLR) method, 11 articles published between 2020-2025 were analyzed through a bibliometric approach and content analysis. The results show that the SSI approach is not only utilized as a learning strategy, but also as a transformative tool that integrates cognitive, affective, and social values aspects. Energy topics and environmental issues dominate the learning context, while other physics topics such as waves and modern physics are less explored. In addition, there is a tendency to apply SSI at the high school level, which is considered more cognitively prepared and reflective. This research recommends diversifying the context of SSI and strengthening teachers' capacity in designing contextual and meaningful physics learning in the post-pandemic era.